Analisis Penugasan Distribusi Dengan Menggunakan Metode Hungarian Pada PT. Air Kristal Lestari Kota Balikpapan (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study is to obtain cost-efficient distribution of system  distribution assignment PT. Air Kristal Lestari in Balikpapan. Analytical methods that used in this study is Hungarian method and processed by using software Production and Operations Management (POM) for Windows. The results showed that the assignment of the distribution system on PT. Air Kristal Lestari is still not efficient, this is visible from the total distribution costs incurred by the company for the fifth car boxes to five locations are greater, namely Rp 1.338.588,- per day, while the results of this research only Rp 1.275.388,- per day. From this research, the difference of cost distribution Rp 63.200,-, so in a month companies can save Rp 758.400,- (Rp 63.200,- X 12 times shipping).Keywords : Assignment, Distribution, Hungarian Method.